IMPLEMENTASI SERTIPIKAT ELEKTRONIK DI INDONESIA: ANALISIS KENDALA DAN PERBANDINGAN DENGAN AUSTRALIA - Ladia, Farhatin; Rosinta, Maya; Suryani, Suryani; Samosir, Tetti (Universitas Labuhanbatu, 2025)
The implementation of electronic land certificates in Indonesia is still facing various obstacles that hinder the full realization of this policy. As part of the digital reform in land administration, the government has issued Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Regulation No. 3 of 2023 on the Issuance of Electronic Documents in Land Registration Activities. However, its enforcement has not been optimal due to technical, regulatory, and institutional challenges. In contrast, Australia has successfully implemented electronic land certificates since 2011, initiated through the Inter-governmental Agreement (IGA), which established regulatory harmonization among its states and territories. This article aims to analyze the challenges of implementing electronic certificates in Indonesia and to examine Australia’s experience as a comparative reference. The research applies a normative juridical method using statutory and comparative approaches. The findings highlight that Indonesia may learn from Australia’s experience, particularly in terms of regulatory harmonization, technological infrastructure readiness, and the enhancement of public legal literacy to support the successful adoption of electronic land certificates. Keywords: Electronic Certificates; Implementation; Land Registration; Comparative Law.